2016
DOI: 10.1002/mus.25197
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal nerve palsy: 245 cases

Abstract: The most frequent etiologies and disease categories of CN XII palsy were identified, and male gender and personal history of cancer were found to be predictive of a neoplastic cause of CN XII palsy. Muscle Nerve 54: 1050-1054, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 3 publications
0
33
0
4
Order By: Relevance
“…En este estudio la principal etiología es la iatrogénica postoperatoria (29.3%), seguida de la idiopática (15.1%) y la neoplásica primaria (14.2%). Entre otras etiologías se encuentran la tumoral metastásica (13%), inflamatoria (7,3%), radiación (6.1%) y traumática (4,1%) [8]. En los últimos años ha cobrado importancia la etiología idiopática.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En este estudio la principal etiología es la iatrogénica postoperatoria (29.3%), seguida de la idiopática (15.1%) y la neoplásica primaria (14.2%). Entre otras etiologías se encuentran la tumoral metastásica (13%), inflamatoria (7,3%), radiación (6.1%) y traumática (4,1%) [8]. En los últimos años ha cobrado importancia la etiología idiopática.…”
Section: Discussionunclassified
“…En la última gran serie publicada, la causa más frecuente de daño del nervio hipogloso es la iatrogénica tras una intervención quirúrgica [8]. Este daño depende del tipo de cirugía, de cambios posturales del cuello, así como de la propia manipulación de la vía aérea.…”
Section: Discussionunclassified
“…In patients with hypoglossal palsy, the following signs are seen: 148 • Tongue atrophy-45% of patients • Tongue deviation-45%…”
Section: Tonguementioning
confidence: 99%
“…Bilateral affection of the hypoglossal nerve manifests as a complete tongue palsy with consecutive oral dysphagia and dysarthria [ 37 , 27 ]. A 2016 review of 245 cases of hypoglossal nerve palsies revealed 14.2% to be primary neoplastic and 13% due to metastatic malignancy, with the remainder postoperative, inflammatory, and secondary to radiation and trauma [ 39 ]. Male gender and a personal history of malignancy are hypothesized to predict a neoplastic source of cranial nerve XII palsy [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%